2011
DOI: 10.1016/j.stem.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

p57 Is Required for Quiescence and Maintenance of Adult Hematopoietic Stem Cells

Abstract: Quiescence is required for the maintenance of hematopoietic stem cells (HSCs). Members of the Cip/Kip family of cyclin-dependent kinase (CDK) inhibitors (p21, p27, p57) have been implicated in HSC quiescence, but loss of p21 or p27 in mice affects HSC quiescence or functionality only under conditions of stress. Although p57 is the most abundant family member in quiescent HSCs, its role has remained uncharacterized. Here we show a severe defect in the self-renewal capacity of p57-deficient HSCs and a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
295
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(323 citation statements)
references
References 30 publications
26
295
2
Order By: Relevance
“…In addition, the defective quiescence phenotype of p57 Kip2 -deficient HSCs is exacerbated by concomitant deletion of either p21 Cip or p27 Kip1 , and p27 Kip1 overexpression is able to compensate for the loss of p57 Kip2 (Matsumoto et al, 2011;Zou et al, 2011). Taken together, these studies reveal p57 Kip2 as a critical regulator of HSC quiescence in adult mice, and suggest some degree of functional redundancies among the CIP/KIP family of CKIs.…”
Section: Cell-intrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 78%
See 1 more Smart Citation
“…In addition, the defective quiescence phenotype of p57 Kip2 -deficient HSCs is exacerbated by concomitant deletion of either p21 Cip or p27 Kip1 , and p27 Kip1 overexpression is able to compensate for the loss of p57 Kip2 (Matsumoto et al, 2011;Zou et al, 2011). Taken together, these studies reveal p57 Kip2 as a critical regulator of HSC quiescence in adult mice, and suggest some degree of functional redundancies among the CIP/KIP family of CKIs.…”
Section: Cell-intrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 78%
“…hematopoietic-specific deletion of p57 Kip2 in adult mice suggests that p57 Kip2 is in fact critical for maintaining HSC quiescence (Matsumoto et al, 2011). In addition, the defective quiescence phenotype of p57 Kip2 -deficient HSCs is exacerbated by concomitant deletion of either p21 Cip or p27 Kip1 , and p27 Kip1 overexpression is able to compensate for the loss of p57 Kip2 (Matsumoto et al, 2011;Zou et al, 2011).…”
Section: Cell-intrinsic Mechanisms Regulating Hsc Quiescencementioning
confidence: 99%
“…Although the suppression of p57kip2 was most remarkable, this would not account for the enhanced self-renewal activity of Fbxl10 Tg HSCs because a previous report showed that p57kip2 was required for HSC quiescence and its deficiency abrogated the self-renewal capacity of HSCs in mice. 23 To identify the differentially regulated functional networks accounting for growth advantage of HSCs in Tg mice, we applied gene set enrichment analysis (GSEA) to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, a database that represents molecular interaction networks, including metabolic pathways, regulatory pathways, and molecular complexes. This analysis revealed that in nonleukemic Tg HSCs, several gene sets were significantly upregulated with "oxidative phosphorylation (OXPHOS)" being the highest ( Figure 4A; Table 2), whereas no gene sets were significantly downregulated, as compared with the control HSCs.…”
Section: Transgenic Expression Of Fbxl10 Induces Proliferation Advantmentioning
confidence: 99%
“…Together, our data reveal a transcriptional network between TGFÎČ, Smad4, Smad7, Gata2, and p57, important for the regulation of hematopoietic progenitor cell proliferation. 18 Figure legends …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p57-deficient HSCs show a severely decreased self-renewal capacity and a reduced proportion of quiescent cells 18 , suggesting that TGFÎČ has a role in keeping HSCs in a quiescent state through a mechanism involving the transcriptional activation of p57.…”
Section: Introductionmentioning
confidence: 99%